Envisioning the World: Mapping and Making the Global - Holtgreve, Sandra; Preuß, Karlson; Albert, Mathias (Global Studies, 2021)
The »global« is permanently made and remade by how it is envisioned in political projects, in language, and in literature. Through a range of case studies, this book shows how practices of referring to the world actually constitute the global in its many facets. It aims to provide a sense in readers of how the global is not something »out there«, but that it is embedded in a wide range of the seemingly »everyday«. The contributions appeal to a readership from a background in Sociology, History, Political Science, Literary Studies, and Social Work.